Analisis Nilai Pendidikan Agama Hindu Dalam Geguritan Atma Prasangsa - Dewa Ayu Made Fitri Wahyuni; I Ketut Tanu; I Made Luwih (Cetta: Jurnal Ilmu Pendidikan, 2019)
The customs and religious systems are still maintained in Bali that are always accompanied by the implementation of yadnya, so the existence of geguritan still has a very important function in the lives of people in Bali. One of them is Geguritan Atma Prasangsa which is full of the noble values ​​in the teachings of Hinduism namely the teachings of Tattwa, Susila, and Events which are the three basic frameworks of Hinduism, all three are an inseparable unity and underlie the religious acts of Hindus. Karma Phala is one of the five beliefs of Hinduism (Panca Sradha). Geguritan Atma Prasangsa tells the story of the Atma's journey to heaven with Karma Phala or the results of the deeds he had during his life. This research approach is qualitative, from primary data obtained through field research and secondary data obtained from several library documentation. To obtain data about Geguritan Atma Prasangsa researchers applied data collection methods with methods of observation, interviews, literature and documentation. After the data is obtained, it is analyzed by qualitative analysis techniques which include, data reduction, data classification, display of data, and conclusions. The results of this study are (1) The narrative structure of Geguritan Atma Prasangsa which includes, synopsis, characterization, incident, plot, message, topic and background. (2) The values ​​of Hindu religious education contained in Geguritan Atma Prasangsa which include Tattwa Education Value, Ethical Education Value, and Ceremony. (3) Implementation of Hindu Education Values, namely: Implementation of Tattwa Education Values, one of which is related to Panca Sradha namely believing in the existence of Brahman, Implementation of the Value of Ethical Education, and Implementation of Educational Values ​​for Ceremonies.